POLYCYSTIC OVARIAN SYNDROME (PCOS) AND ITS IMPACT ON MENTAL HEALTH: A CROSS-SECTIONAL STUDY IN PESHAWAR, PAKISTAN - Mehtab Shah; Shireen Baqir; Heera Urooj; Shazma Shah; Ali Ahsan Mufti; Sumera Qayyum (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder that significantly affects the quality of life of women in the child-bearing period. However, there are many signs of PCOS such as hirsutism, infertility, insulin resistance, but the underlying psychological aspect of the disorder is relatively unknown especially in the culturally conservative environment of Peshawar city in Pakistan. This study aims to quantify the levels of anxiety, depression and loneliness among females with PCOS in Peshawar to quantify the levels of anxiety, depression and loneliness among women With PCOS in Peshawar to determine socio-demographic and lifestyle correlates of these outcomes among females with PCOS in Peshawar.Methods: Four hundred and ten women diagnosed with polycystic ovary syndrome (PCOS) from lady Reading Hospital Peshawar, participated in the study, which used a cross-sectional survey approach. The UCLA Loneliness Scale (V3), the Generalised Anxiety Disorder 7-item (GAD-7 scale), and the Patient Health Questionnaire 9 (PHQ-9) were utilised for screening patients' mental health state. Using SPSS version 26, we ran chi-square tests and logistic regression to see how different socio-demographic factors correlated with different lifestyle and mental health outcomes.Results: The findings of this research showed that 55% of the participants were lonely, 65% had anxiety symptoms which fall under the category of Generalized Anxiety Disorder, and 45% presented with depressive symptoms which belong to the Depressive Disorder category. Positive significant relationships to BMI, marital status, education, economic status and life style behavior of these mental health problems were established. In logistic regression analysis, irregular meal pattern, junk food intake and less BMI were found to have influence in mental health. It was also noted that those who lived with their families or women with higher economic background tended to have anxiety.Conclusions: The results show the existing high rate of mental health issues among women managing PCOS in Peshawar. Multidimensional bio-psychosocial management of PCOS is recommended in order to enhance the treatment outcomes of these patients in this region.